Recent Advances in Ophthalmic Drug Delivery - Anuj Chauhan; Laurence Fitzhenry; Ana Paula Serro (MDPI AG, 2022)
Due to population aging and to the increasing prevalence of diseases such as diabetes, chronic eye disorders such as glaucoma, age-related macular degeneration, and diabetic retinopathy have increased significantly, becoming responsible for a high percentage of blindness and vision impairment cases at a global level [...]